A new route to nitrogen heterofullerenes and the first synthesis of (C69N)2 - Nuber, Berthold; Hirsch, Andreas (Chemical Communications, 1996)
Heating butylamino adducts of diazabis-(1,6);(1,9)-homofullerenes bearing MEM-protected imino bridges with toluene-p-sulfonic acid provides a new route to (CN) in macroscopic amounts and also provides, for the first time, the synthesis and isolation of (CN) and the heterofullerene adducts RCN and RCN.